2021
DOI: 10.1111/jocd.14602
|View full text |Cite
|
Sign up to set email alerts
|

Treatment protocols and efficacy of combined laser with medical treatment modalities in vitiligo

Abstract: Vitiligo is an acquired immune-mediated pigmentary skin disease affecting 1%-2% of worldwide population. 1 First-line therapy for restricted and extensive involvement is topical therapy (corticosteroids [TCS] and calcineurin inhibitors [TCI, tacrolimus, and pimecrolimus]) and narrow-band ultraviolet B (NB-UVB), respectively. 2-5 Nowadays, lasers are used for treatment of difficult-to-treat areas and refractory lesions. Monochromatic excimer laser (MEL)/excimer light (EL) was the first laser used in treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Another recent approach involves using lasers (excimer, CO 2 , Er:YAG, and non‐ablative resurfacing laser), even combined with topical treatments 5,6 …”
Section: Introductionmentioning
confidence: 99%
“…Another recent approach involves using lasers (excimer, CO 2 , Er:YAG, and non‐ablative resurfacing laser), even combined with topical treatments 5,6 …”
Section: Introductionmentioning
confidence: 99%
“…Besides systemic medications, surgical grafting and discoloration, topical medications and phototherapy are the first-line treatment of vitiligo. 6,7 The two most common topical drugs are glucocorticoid and calcineurin inhibitors. The therapeutic effect of the topical calcineurin inhibitor (TCI) is equal to the potent topical steroid, 8 but TCI does not have any glucocorticoid adverse reactions such as telangiectasia, hairy and skin atrophy.…”
Section: Introductionmentioning
confidence: 99%
“…Phototherapy combined with other treatments can provide higher efficiency, quicker onset of action and better adherence to treatment. 6 Since Kawalek et al 14 first reported the synergistic effect of topical tacrolimus combined with 308-nm EL in 2004, many studies have demonstrated that 308-nm EL combined with TCI is more efficient than 308-nm EL monotherapy in the treatment of vitiligo. [15][16][17][18][19][20] However, there is no literature illuminating combined therapy is better for the special vitiligo region like the periocular skin.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations